2014
DOI: 10.1136/bjophthalmol-2014-306054
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum ofCYP1B1in Chinese patients with primary open-angle glaucoma

Abstract: This study provides a mutation spectrum of CYP1B1 resulting in POAG development in a Chinese population, which may demonstrate an involvement of the gene in a proportion of subjects with POAG and help to improve our understanding of the pathogenesis of CYP1B1-associated POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Glaucoma is a heterogeneous disease that represents the second primary cause of irreversible loss of eyesight worldwide [23,24]. Globally, ~64.3 million individuals are diagnosed with glaucoma.…”
Section: Cyp1b1 In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Glaucoma is a heterogeneous disease that represents the second primary cause of irreversible loss of eyesight worldwide [23,24]. Globally, ~64.3 million individuals are diagnosed with glaucoma.…”
Section: Cyp1b1 In Glaucomamentioning
confidence: 99%
“…This prevalence is anticipated to increase to 76 million in 2020 [25] and 111.8 million in 2040 [26]. Glaucoma is a nonuniform group of neurodegenerative ocular disorders [27] characterized by several clinical features that include visual field defects, retinal ganglion cell death, and progressive degeneration of the optic nerve [23]. The primary source of the progressive degeneration of the optic nerve is the occurrence of a lesion in the axons of the retinal ganglion cells [28].…”
Section: Cyp1b1 In Glaucomamentioning
confidence: 99%
“…Several studies have reported that POAG patients express only mutated CYP1B1 (Melki et al, 2004;Lopez-Garrido et al, 2006;Chakrabarti et al, 2007;Kumar et al, 2007;Suri et al, 2008;Hilal et al, 2010;Lopez-Garrido et al, 2010;Milla et al, 2013;Zhou et al, 2013). Some studies have also observed an association between single nucleotide polymorphisms (SNPs) in the CYP1B1 gene and POAG incidence (Melki et al, 2005;Acharya et al, 2006;Bhattacharjee et al, 2008;Burdon et al, 2010;Fan et al, 2010;Patel et al, 2012;Buentello-Volante et al, 2013;Gong et al, 2015;Micheal et al, 2015;Williams et al, 2015). On the other hand, a meta-analysis conducted by Dong et al (2012) showed the absence of any correlation between POAG and polymorphisms at the SNP sites rs1056836, rs10012, rs1056837, rs1056827, rs2567206, and rs180040.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, nine identified loci provided additional ophthalmological diagnostic information. For instance, OPA3 mutations are associated with optic atrophy [24], BEST1 mutations are associated with best vitelliform macular dystrophy (BEST) [27][28][29][30], TSPAN12 mutations are associated with familial exudative vitreoretinopathy (FEVR) [35], PAX6 mutation are associated with aniridia and Peter's anomaly [48], and CYP1B1 mutations are associated with glaucoma [45]. In addition, we also identified a monoallelic mutation in BMP4, which has been mostly associated with microphthalmia [40] or facial clefts [49].…”
Section: Discussionmentioning
confidence: 84%